High quality interconnected core/shell ZnO nanorod architectures grown by pulsed laser deposition on ZnO-seeded Si substrates. (January 2017) - Inguva, Saikumar; Vijayaraghavan, Rajani K.; McGlynn, Enda; Mosnier, Jean-Paul
Abstract: We report the production of vertically aligned and interconnected ZnO core/shell nanorods using pulsed laser deposition (PLD) in a continuous two-step growth process. X-ray diffraction studies showed wurtzite structure and c -axis orientation with a high degree of verticality. Scanning electron microscopy showed a characteristic interconnection morphology between the nanorod tips uniformly present over the entire sample surface area, while transmission electron microscopy revealed crystalline core/amorphous shell architecture. Strong bands at 98.7 cm −1 and 437.2 cm −1 (wurtzite ZnO low and high non-polar E2 modes) were the main features of the nanorod Raman spectra, again showing the high sample quality. Low-temperature PL data exhibited strong I6 emission and structured green band showing high optical quality. Electrical studies indicated n -type material with ohmic behaviour. The results are discussed in the context of the advantages offered by interconnected architectures of core/shell ZnO nanostructures for various applications. Highlights: Growth of high quality vertically aligned and interconnected ZnO core/shell nanorods. Growth by catalyst-free PLD in a continuous two-step growth process. Nanorods show good crystalline quality with a high degree of verticality. Nanorods show excellent uniformity, optical and electrical properties.